Automatic Local Coordinates Evaluating and automating methods to estimating 3D coordinates with respect to a specific Datum - Couto, Rafael Gonçalves (2019)
The physical location of a specific point in the globe does not has the same coordinates as time passes by. This is due to the movement of the tectonic plates. The physical point, observed in a specific day, changes as function of time and consequently its precise coordinates change as well. However, for many geo-referencing applications (mapping, navigation, etc.) it is preferable to consider static reference frames such as the system currently in force in Portugal (PT-TM06 / ETRS). To obtain the coordinates of a point in relation to a static reference frame it is necessary: (1) processing the observation data, and (2) convert this data for the selected reference datum. For processing the observation data it is possible to use online GNSS data processing services. These are simple to use and provide this type of post-processing to groups with lower financial resources and / or specific expertise. However, these require converting the results of the online services from the used datum (usually the materialization of the last ITRF at the time of observation) to the desired reference datum. This is accomplished through the calculation and application of transformation parameters to the coordinates obtained in the online processing. This thesis presents in detail the implementation of a solution that aims to automate the entire process of calculating coordinates in a given datum reference (usually national) using online pro¬cessing services. The application to Portugal was used as case study, using the National Network of GNSS Permanent Stations (ReNEP), which is managed by the Direcção Geral do Território to materialize the reference datum. The focus of this work has been more focused on informatics component, however other studies were also conducted that allowed to the evaluation of the quality of the obtained coordinates and to define some of the parameters required to optimize these. To obtain the coordinates of the final system (for Portugal, the national materializa¬tion of ETRS89) it was necessary to develop several tools, which were subsequently tested and validated, and consist in: • Automatic GNSS data processing using online processing services; • Gross error detection (outliers) and formal error normalization given by online services; • Calculation and subsequent application of coordinate transformation parameters; • Development of a web service to be provided to the community. ln the developed tools there is still room for expansion (such as adding more online services) and improvement of some features (such as automatic integration with the MGN application (GNSS Networks Management) and automatic detection of errors in the reference stations). However, the objectives have been achieved and currently, the tool and the web service are available in operating mode (although not yet officially released), hosted in SEGAL servers ready to be tested by the community. It also planned to test the implementation of the ALC in other countries (eg. Mozambique, Bhutan).